Interfacial Energy Level Alignment and Defect Passivation by Using a Multifunctional Molecular for Efficient and Stable Perovskite Solar Cells - Ye, Yong‐Chun; Chen, Li; Chen, Xian‐Min; Ma, Chun‐Ying; Lv, Bing‐Hao; Wang, Jiang‐Ying; Dou, Wei‐Dong; Zhang, Chu; Ma, Ting‐Li; Tang, Jian‐Xin (Advanced functional materials, 2024)
Tin oxide (SnO2) is currently the dominating electron transport material (ETL) used in state‐of‐the‐art perovskite solar cells (PSCs). However, there are amounts of defects distributed at the interface between ETL and perovskite to deteriorate PSC performance. Herein, a molecule bridging layer is built by incorporating 2,5‐dichloroterephthalic acid (DCTPA) into the interface between the SnO2 and perovskites to achieve better energy level alignment and superior interfacial contact. The multifunctional molecular bridging layer not only can passivate the trap states of Sn dangling bonds and oxygen vacancies resulting in improved conductivity and the electron extraction of SnO2 but also can regulate the perovskite crystal growth and reduce defect‐assisted nonradiative recombination due to its strong interaction with undercoordinated lead ions. As a result, the DCTPA‐modified PSCs achieve champion power conversion efficiencies (PCEs) of 23.25% and 20.23% for an active area of 0.15 cm2 device and 17.52 cm2 mini‐module, respectively. Moreover, the perovskite films and PSCs based on DCTPA modification show excellent long‐term stability. The unencapsulated target device can maintain over 90% of the initial PCE after 1000 h under ambient air. This strategy guides design methods of molecule bridging layer at the interface between SnO2 and perovskite to improve the performance of PSCs . A multifunctional molecular bridging layer using 2,5‐dichloroterephthalic acid as a pre‐buried additive on the tin oxide (SnO2) electron transport layer enables interfacial energy level alignment and defect passivation. As a result of the method, the high power conversion efficiencies of 23.25% and 20.23% for the active area of 0.15 cm2 device and 17.52 cm2 mini‐module are achieved, respectively.